Possible electronic mechanisms of generation and quenching of luminescence of singlet oxygen in the course of photodynamic therapy: ab initio study - Minaev, B.F.; Yashchuk, L.B. (Біополімери і клітина, 2006)
On the basis of ab initio quantum chemical calculations the strong enhancement of the ¹(a1Δg·S₀)→ ¹(X³Σg– ·T) transition in collision complex between O₂ and organic dye is predicted, where T is the triplet excited state of the dye and S₀ is its ground singlet state. The collision-induced electric dipole transition moment depends on polarizability of the dye and can be used for the estimation of energy transfer rate constant. Quantum chemical calculations can predict the most efficient dye sensibilizer for photodynamic therapy of cancer, instead of the difficult experimental search. Some new ideas are proposed for additional laser simulated mechanisms of active oxygen generation. На основі ab initio квантово-хімічних розрахунків передбачено істотне зростання ¹(a1Δg·S₀)→ ¹(X³Σg– ·T) переходу в комплексі зіткнення O₂ з органічним барвником, де Т — це триплетний збуджений, a S₀ — основний синглетний стан барвника. Індукований зіткненням електродипольний момент переходу залежить від поляризованості барвника і може бути використаний для оцінки констант перенесення енергії. Квантово-хімічними розрахунками можна точніше передбачити найефективніший барвник-сенсибілізатор для фотодинамічної терапії рака, ніж складними експериментальними дослідженнями. Запропоновано деякі нові ідеї стосовно механізмів додаткового моделювання стадії активації кисню. На основании ab initio квантово-химических расчетов предсказано сильное увеличение ¹(a1Δg·S₀)→ ¹(X³Σg– ·T) перехода в комплексе столкновения O₂ с органическим красителем, где Т — триплетное возбужденное, a S₀ — основное синглетное состояние красителя. Индуцированный столкновением электродипольный момент перехода зависит от поляризуемости красителя и может быть использован для оценки констант переноса энергии. Квантово-химическими расчетами можно точнее предсказать наиболее эффективный краситель-сенсибилизатор для фотодинамической терапии рака, нежели сложными экспериментальными исследованиями. Предложены некоторые новые идеи относительно механизмов дополнительного моделирования стадии активации кислорода